Tunnelling effects on capped piles and masonry buildings with shallow strip foundations - Tang, Chuanjin (2024)
The increasing demand for infrastructure space in urban areas presents enormous prospects and challenges for the expansion and utilisation of underground spaces. Tunnels are a common way to utilise underground space, yet tunnel excavations are often situated close to existing underground and surface structures (such as piles, strip foundations, and masonry buildings) and bring potential risks to these structures. Therefore, it is important to understand soil-structure interaction mechanisms in tunnelling scenarios to provide a reference for designing new tunnels near deep pile foundations or under masonry buildings with shallow strip foundations. Nevertheless, due to the complexity of actual engineering projects, few studies have accurately investigated the comprehensive tunnel-soil-pile interaction (TSPI) and tunnel-soil-masonry building interaction with shallow strip foundation (TSBI) problems.